Outcomes of 25 female dogs treated for ectopic ureters by open surgery or cystoscopic‐guided laser ablation. Issue 4 (29th March 2022) - Dekerle, Bastien; Maurice, Emeline; Decambron, Adeline; Viateau, Véronique; Maurey, Christelle; Manassero, Mathieu
Abstract: Objective: To report outcomes after the correction of ectopic ureter (EU) by open surgery or cystoscopic‐guided laser ablation (CLA) in female dogs. Study design: Retrospective study from 2011 to 2018. Animals: Twenty‐five female dogs. Methods: Data collected included signalment, clinicopathologic data, procedural data, complications, and short‐term and long‐term outcomes. Complications were graded as minor or major if a surgical revision was required. Continence status was scored subjectively (1 = completely incontinent to 10 = fully continent). Results: Fifteen dogs had bilateral EU and 24 had intramural EU (iEU). Open surgical correction included 13 neoureterostomies, 2 neocystoureterostomies, and a combination of these in 2 dogs. Eight dogs underwent CLA. Eighteen dogs experienced minor complications (72%), and 2 experienced major complications (8%). One‐month postoperative continence was achieved in 20/25 (80%) dogs (median score of 10). Incontinence recurred at a median time of 24.9 months in 5 dogs but responded to medical treatment. Overall, dogs remained continent for 66 months (median) and 22/25 (88%) dogs achieved continence with adjunction of medical/surgical treatment in incontinent ones. Fewer minor complications and postoperative recurrences of incontinence were documented after CLA than neoureterostomy ( P < .01 and P < .05). Conclusion: Ectopic ureter correction by open surgery or CLA resulted in a subjectively good prognosis, most dogs reaching continence within a month of surgery, although incontinence occasionally recurred in the long term. CLA was associated with fewer complications and incontinence recurrences than neoureterostomy. Clinical significance: Cystoscopic‐guided laser ablation should be preferred to correct iEU to prevent short‐term complications and the recurrence of incontinence. Further studies should investigate the cause of postoperative recurrence of urinary incontinence.